The role of the Tatar educational elite in the formation of national socio-political thought at the turn of the XIX-XX centuries (modern research aspects) - Akhmetova, Albina R. (2021)
At the end of the 20th century, changes took place in the world that forced politicians and scientists to rethink many seemingly established postulates about the laws of social life and about the ways of development of human civilization. The modern development of the social movement among the Tatars of Russia, and especially the national processes in Tatarstan largely repeat the trends in the development of the nation in the pre-Soviet period. The main role in the social movement of nations is played by the activities of the elite aimed at creating political, educational and cultural institutions. The turning point in the history of the Tatar people should be considered the end of the 19th - the beginning of the 20th century. The Tatar ideology was created during the period of rapid development of bourgeois socio-economic relations (especially noticeable among the Tatars of the Volga-Ural region) and the rise of national culture. However, until recently, the sources and works of authors of different times have not been fully studied, although they contain data on the processes of formation of the Tatar social factor and the Tatar nation itself in the context of the development of the Russian community.